(untitled) (Czech Journal of International Relations, 2024)
Storytelling is an essential aspect of the creation of a community of the mind. Shortly after its invention, film became instrumental in cultivating national identity. States and national groups are keen to have their stories told in order to reinforce a sense of identity internally and claim relevance externally. This paper explores how film and popular culture help to explain politics and identity in Ukraine, examining how films are reinterpreted, reformulate a canon, and facilitate new political arguments. Therefore, through the films of Alexander Dovzhenko, we can see how the struggle to balance political ideology and national identity depicted in them helps to illuminate and explain politics today. A feature of Ukrainian cinema that is often overlooked is how films made by the diaspora perpetuated national identity, language, and culture through periods of hunger and subjugation. These films are both a statement of political and cultural identification and the basis for current political claims.